2006
DOI: 10.1143/jjap.45.2945
|View full text |Cite
|
Sign up to set email alerts
|

Negative Bias Temperature Instability Dependence on Dielectric Thickness and Nitrogen Concentration in Ultra-scaled HfSiON Dielectric/TiN Gate Stacks

Abstract: Negative bias temperature instability (NBTI) of the HfSiON/TiN gate stack is investigated as a function of the dielectric thickness. It is shown that as the thickness of the HfSiON layer is reduced below 20 Å , the NBTI mechanism approaches the mechanism that induces H-reaction diffusion. Conversely, for thicker HfSiON dielectrics, a combination of H-reactiondiffusion and charge detrapping from the bulk HfSiON contribute to NBTI. MOS devives with plasma nitrided HfSiON (30 Å) with varying nitrogen (N) content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
(6 reference statements)
0
9
0
Order By: Relevance
“…The second approach to avoid the damage from ion implantation was generally to use the N 2 plasma treatments [34][35][36] or postdeposition annealing ͑PDA͒ in nitrogen ambient, such as N 2 , NO, N 2 O, or HH 3 . 37,38 In this work, we use N 2 O plasma treatment ͑at…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second approach to avoid the damage from ion implantation was generally to use the N 2 plasma treatments [34][35][36] or postdeposition annealing ͑PDA͒ in nitrogen ambient, such as N 2 , NO, N 2 O, or HH 3 . 37,38 In this work, we use N 2 O plasma treatment ͑at…”
Section: Resultsmentioning
confidence: 99%
“…The second approach to avoid the damage from ion implantation was generally to use the N 2 plasma treatments [34][35][36] or postdeposition annealing ͑PDA͒ in nitrogen ambient, such as N 2 , NO, N 2 O, or HH 3 . 37,38 In this work, we use N 2 O plasma treatment ͑at bulk and also introduce nitrogen ͑radical of nitrogen in N 2 O plasma͒ in the bulk. Figure 7 shows the SIMS profile for samples with N 2 O plasma treatment ͑20 W͒.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed description of the gate dielectric manufacturing process is provided in Ref. [4]. Devices with gate lengths of 1.0 lm and 0.7 lm, both with 0.5 lm gate widths, were measured; the two gate length sets gave similar results.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that HKMG devices have n ∼ 0.16 and this value could be obtained when both interface trap generation at the IL and charge detrapping at the HK layer took place simultaneously. 21) lifetime than SC-1. Therefore, employing O 3 cleaning in forming the IL/HK interface effectively suppresses the NBTI effect by reducing the initial traps.…”
mentioning
confidence: 87%
“…Firstly, energetic holes break the Si-H bonds at the Si/SiO 2 interface, 19,20) and secondly, initial negative fixed charges in the HK layers are detrapped. 21,22) These results indicate that it is crucial to minimize the interface and initial traps when fabricating HK embedded devices. 23,24) Although lots of researches have been focused on the improvement of the IL/HK interface characteristics, the effects of precleaning process in advance to HK deposition has not been studied.…”
mentioning
confidence: 92%